2017
DOI: 10.1080/00140139.2017.1355070
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical investigation of prolonged driving in an ergonomically designed truck seat prototype

Abstract: A postural evaluation during a prolonged driving task was conducted to determine the ergonomic validity of a new freely adjustable truck seat prototype. Twenty participants were recruited to perform two 2-h simulated driving sessions. Postures were assessed using motion capture, accelerometers and pressure pads. Subjective discomfort was also monitored in 15-min increments using ratings of perceived discomfort (RPD) and the Automotive Seating Discomfort Questionnaire. Participants had a more neutral spine post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…A sensitivity analysis was conducted including only the 5 studies that were rated as having an overall low risk of bias (n ¼ 121). 35,38,40,42,43 Also among these studies, an increased pain rating from baseline after sitting exposure was also observed.…”
Section: Quality Of Reporting Risk Of Bias Assessment and Synthesismentioning
confidence: 71%
See 4 more Smart Citations
“…A sensitivity analysis was conducted including only the 5 studies that were rated as having an overall low risk of bias (n ¼ 121). 35,38,40,42,43 Also among these studies, an increased pain rating from baseline after sitting exposure was also observed.…”
Section: Quality Of Reporting Risk Of Bias Assessment and Synthesismentioning
confidence: 71%
“…The titles and abstracts of the 361 remaining articles were screened, and of these, 75 full papers were accessed for further review of eligibility. Sixty-five articles were excluded and the remaining 10 articles, 21,[35][36][37][38][39][40][41][42][43] including data for 330 participants, were included in this study (Fig 1).…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations